Optogenetic dissection of the dopaminergic circuitry involved in memory consolidation - Duszkiewicz, Adrian Jacek (The University of Edinburgh, 2016)
The ‘synaptic tagging-and-capture’ (STC) theory of cellular memory consolidation holds that memory persistence can be altered by prior or subsequent patterns of neural activity (Redondo & Morris 2011). The aim of this thesis was to develop a realistic model of everyday memory for mice and use the optogenetic toolbox to investigate the neuromodulatory circuitry that modulates persistence of everyday spatial memories. The task involved learning a win-stay rule with the daily goal of finding the location of food in the event arena. Using the developed task, it was confirmed that unrelated novel experiences can facilitate the persistence of spatial memory in a manner sensitive to pharmacological blockade of hippocampal dopamine D1/D5 receptors. Further analysis focused on identifying the specific neuromodulatory systems that mediate this effect. An influential model called the ‘hippocampus- VTA loop’ (Lisman & Grace 2005) points to the critical role of dopaminergic neurons in the ventral tegmental area (VTA), but recent evidence also implicates locus coeruleus (LC) as a potential source of dopamine in the hippocampus (Smith & Greene 2012). In order to identify the dopaminergic structure(s) that may mediate the novelty effect on memory persistence, single unit activity of optogenetically identified catecholaminergic (CAergic) neurons in mouse VTA and LC was recorded in a novelty exploration paradigm. Using tyrosine hydroxylase-Cre knock-in mice and a Cre-dependent adeno-associated viral vectors, CAergic neurons in VTA and LC were selectively tagged with channelrhodopsin-2 (ChR2). Conditional ChR2 expression made it possible to reliably identify CAergic neurons during unit recording sessions in freely moving animals. The main conclusion of the study is that that CAergic neurons in both VTA and LC selectively increase their firing rates in novel environments, relative to both a familiar environment and a home cage baseline. When normalised to their average baseline firing rates, LC neurons are more strongly activated by novelty than VTA neurons. In the final experiment outlined in this thesis, another cohort of Th-Cre mice, in which ChR2 was expressed in CAergic neurons of both VTA and LC using a Cre-dependent adeno-associated virus, was trained on the everyday appetitive spatial memory task. ChR2-mediated photoactivation of CAergic neurons in LC but not in VTA 30 min after encoding, substituting for novelty, was successful in enhancing the persistence of memory. Paradoxically, the effect of optogenetic LC activation was blocked by hippocampal microinfusion of dopamine D1/D5 receptor antagonist but not β-adrenergic receptor antagonist. Results of experiments described in this thesis support the principle of STC theory and collectively indicate that dopamine released from hippocampal terminals of LC neurons mediates the novelty effect on memory persistence. Importantly, they also point to a more general of role of LC in gating of entry to long-term memory.
Keywords: dopamine; memory; locus coeruleus; novelty